Study of Variability of Atmospheric Ozone over Jumla in Half Period of 24 Solar Cycle - Shrestha, P. M.; Chapagain, N. P.; Karki, I. B.; Poudyal, K. N. (Journal of Nepal Physical Society, 2021)
This paper reports the variation of total ozone column (TOC) over Jumla (Lat.:-29.28° N, Long.:-82.16° E and Alt.:- 2300 m above sea level) from 2008 to 2014 derived from Total Ozone Mapping Spectrometer (TOMS) satellite observations. The monthly, seasonal, annual variations of TOC, solar insolation and clearness index have been analyzed. The result exemplifies that during the whole study period, the maximum value of monthly average TOC is 289.21 DU ± 10.75 DU in April, while the minimum value is 257.23 DU ± 11.25 DU in December. The results also show that TOC is highly seasonal dependent with larger TOC in spring 273.68 DU ± 14.92 DU and lower in the winter season (260.68 DU ± 15.25 DU). The average annual value of TOC exhibits slightly variable with a maximum in 2010 (277.52 DU ± 40.64 DU) and minimum in 2008 (267.19 DU ± 11.11 DU). The average values of solar insolation and clearness index for whole study the period are 5.10 86 kWh/m2/day ± 0.86 kWh/m2/day and 0.59 ± 0.12 respectively. The average value of TOC during the whole study period is 271.84 DU ± 14.19 DU, which indicates a good amount of stratospheric ozone content over Jumla.